Feed resources for rearing livestock in the Bundelkhand region of Uttar Pradesh - SARAN, SANDEEP; SINGH, R A; SINGH, RAIVIR; RANI, S ISABELLA; SINGH, K K (The Indian Journal of Animal Sciences, 2013)
A survey of 120 samples in the Bundclkhand region of Uttar Pradesh conducted during 1996-97 revealed that crop residues constituted the major feed resources for the domesticated livestock population. Berseem as green fodder and wheat and peas straw (dry fodder) constituted over 41 %,40% and 13%, respectively, of total livestock feed availability from the cultivated sources during raM Sorghum (green) contributed about 58% of total kharif availability of livestock feed from cultivated sources followed by crop residues of soybean (21.63%) and black gram (16.68%). More than 88% of annual availabIlity of dry fodder and 86% of green fodder was obtai ned during rabi season itself. Anna pratha - system of leaving the livestock free for grazing was commonly practiced during lean scasons as also during rainy season. Soaked oil-cukes and concentrates mixed with dry fodder (wheat and peas straw) were also offered to the milch animals during the periods of green fodder scarcity.